E2F1-mediated upregulation of p19INK4d determines its periodic expression during cell cycle and regulates cellular proliferation - Carcagno, A.L. (2011)
Background: A central aspect of development and disease is the control of cell proliferation through regulation of the mitotic cycle. Cell cycle progression and directionality requires an appropriate balance of positive and negative regulators whose expression must fluctuate in a coordinated manner. p19INK4d, a member of the INK4 family of CDK inhibitors, has a unique feature that distinguishes it from the remaining INK4 and makes it a likely candidate for contributing to the directionality of the cell cycle. p19INK4d mRNA and protein levels accumulate periodically during the cell cycle under normal conditions, a feature reminiscent of cyclins. Methodology/Principal Findings: In this paper, we demonstrate that p19INK4d is transcriptionally regulated by E2F1 through two response elements present in the p19INK4d promoter. Ablation of this regulation reduced p19 levels and restricted its expression during the cell cycle, reflecting the contribution of a transcriptional effect of E2F1 on p19 periodicity. The induction of p19INK4d is delayed during the cell cycle compared to that of cyclin E, temporally separating the induction of these proliferative and antiproliferative target genes. Specific inhibition of the E2F1-p19INK4d pathway using triplex-forming oligonucleotides that block E2F1 binding on p19 promoter, stimulated cell proliferation and increased the fraction of cells in S phase. Conclusions/Significance: The results described here support a model of normal cell cycle progression in which, following phosphorylation of pRb, free E2F induces cyclin E, among other target genes. Once cyclinE/CDK2 takes over as the cell cycle driving kinase activity, the induction of p19 mediated by E2F1 leads to inhibition of the CDK4,6-containing complexes, bringing the G1 phase to an end. This regulatory mechanism constitutes a new negative feedback loop that terminates the G1 phase proliferative signal, contributing to the proper coordination of the cell cycle and provides an additional mechanism to limit E2F activity. © 2011 Carcagno et al.